3.40. Dany jest wzór funkcji kwadratowej f w postaci iloczynowej. Podaj wzór funkcji f w postaci kanonicznej. a) f(x) = (x – 1)(x + 5) c) f(x) = 2 * (x – sqrt(6)) ^ 2 e) f(x) = 3/5 * (x – 1) * (x + 5) b) f(x) = 2sqrt(3) * x * (x + 4) d) f(x) = – 1/2 * (x + 6) * (x – 6) f) f(x) = – 2/3 * (x – 3) * (x – 4)

3.40. Dany jest wzór funkcji kwadratowej f w postaci iloczynowej. Podaj wzór funkcji f w postaci kanonicznej. a) f(x) = (x – 1)(x + 5) c) f(x) = 2 * (x – sqrt(6)) ^ 2 e) f(x) = 3/5 * (x – 1) * (x + 5) b) f(x) = 2sqrt(3) * x * (x + 4) d) f(x) = – 1/2 * (x + 6) * (x – 6) f) f(x) = – 2/3 * (x – 3) * (x – 4)